2016
DOI: 10.3906/tar-1404-10
|View full text |Cite
|
Sign up to set email alerts
|

Superparasitism and host discrimination behavior of Eretmocerus warraeNaumann & Schmidt (Hymenoptera: Aphelinidae)

Abstract: Eretmocerus warrae Naumann & Schmidt is a thelytokous parasitoid that attacks the greenhouse whitefly, Trialeurodes vaporariorum. Its host discrimination and superparasitism behavior was investigated at different host densities and time intervals between the first and second ovipositions under laboratory conditions (22 ± 1 °C, 60 ± 5% RH, a 16:8 light:dark photoperiod). At a density of between 10 and 15 hosts, significantly fewer ovipositions in parasitized nymphs were performed by the same experienced parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The pro‐synovigenic nature of the parasitoid is probably the prerequisite for the evolution of this ability. Because newly emerged parasitoids carry a substantial number of mature eggs (≈30), they can either delay or reduce host feeding and focus on parasitization in a competitive environment (high parasitoid density). This strategy is advantageous for the application of the augmentation approach to effective suppression of whitefly populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pro‐synovigenic nature of the parasitoid is probably the prerequisite for the evolution of this ability. Because newly emerged parasitoids carry a substantial number of mature eggs (≈30), they can either delay or reduce host feeding and focus on parasitization in a competitive environment (high parasitoid density). This strategy is advantageous for the application of the augmentation approach to effective suppression of whitefly populations.…”
Section: Discussionmentioning
confidence: 99%
“…Among the six Eretmocerus species that have been reared from T. vaporariorum , E. warrae Naumann and Schmidt (Hymenoptera: Aphelinidae) is a thelytokous (no males) and specialist parasitoid . Like other Eretmocerus species, E. warrae insert their ovipositors and lay eggs between the whitefly nymphs and the leaf surface, eggs hatch under the hosts, and the first instar larvae penetrate the hosts when the latter reach the fourth instar .…”
Section: Introductionmentioning
confidence: 99%
“…Hanan et al [24] who also evaluated the density of the host, Trialeurodes vaporariorum (Westwood, 1856) (Hem. Aleyrodidae) under parasitism of Eretmocerus warrae Naumann & Schimidt, 2000 (Hym.…”
Section: Influence Of Diet and Host Density On Parasitismmentioning
confidence: 99%
“…(Lopez and Botto 1997) and E. eremicus (Gamborena and van Lenteren 2004) as an agent for biological control were studies on greenhouse whitefly. Also, investigation on reproductive biology of E. warrae a thelytokous parasitoid of T. vaporariorum showed that this parasitoid can potentially contribute to biological control of greenhouse whitefly (Hanan 2012). …”
mentioning
confidence: 99%